Analiis Pengaruh Belanja Modal Terhadap Pertumbuhan Ekonomi dan Ketimpangan Pendapatan di Sumatera Barat - Yohana Pranata; Idris Idris (Universitas Negeri Padang, 2021)
This study aims to determine and analyze the effect of capital expenditure on economic growth and income inequality in West Sumatra. This research is descriptive and inductive. The data used in this study is secondary data with data collection using panel data obtained from BPS West Sumatra Province 2014-2018 period with 19 regencies / cities in West Sumatra. This study analyzed using a simultaneous equation model (simultaneous equation regression model). The results of this study indicate that (1) Capital Expenditures have a significant effect on Economic Growth in West Sumatra (2) Capital Expenditures have no significant effect on Income Inequality in West Sumatra (3) Simultaneously Capital Expenditures and Economic Growth have a significant effect on Income Inequality in West Sumatra.